AB0889 Tnfα Blockade is Perspective in Systemic JIA after Partial Effect of Rituximab or TOCILIZUMAB Treatment. (10th June 2014) - Alexeeva, E.; Valieva, S.; Denisova, R.; Bzarova, T.; Isayeva, K.; Chistyakova, E.; Chomahidze, A.; Sleptsova, T.; Mitenko, E.; Fetisova, A.; Lomakina, O.
Abstract : Background: Patients with systemic juvenile idiopathic arthritis (sJIA) may not respond sufficiently to tocilizumab and rituximab therapy. Some patients reached remission of systemic features but had persistent arthritis. In these cases switching to TNFα ingibitor might be beneficial. Objectives: To evaluate efficacy and safety of TNF blockers in the treatment of sJIA refractory to DMARDS, rituximab or tocilizumab. Methods: Patients fulfilling the ILAR classification criteria for sJIA (n=14, boys 5) who were switched from rituximab (n=9) or tocilizumab (n=5) to TNF blockers (adalimumab n=10, etanercept n=4) were enrolled in a prospective observational study conducted in one Russian pediatric center. Patients received concominant therapy: methotrexate (n=2), methotrexate and cyclosporine (n=12), prednisolone (n=1). The mean age was 9, 1 (8; 14, 9) (here and after Me (25;75)), the mean age at disease onset - 2, 1 (1;4, 5) years, mean disease duration - 7 (4; 10)years, the remission of systemic features - 2, 2 (range from 1 to 5 years). Because of persistent arthritis without systemic manifestations antiTNF therapy were initiated after 2, 4 years rituximab and 1, 4 years tocilizumab treatment. The efficacy was evaluated according to the ACR30/50/70/90 paediatric criteria and criteria of remission. The duration of TNFblockers therapy and observation was 2 months (n=14), 6 m (n=11), 12 m (n=7) and 24 m (n=5). Results: The ACR30/50/70/90 improvements were reached by 95/64/50/28% of patients at month 2, by 100/82/73/73% of patients at month 6, by 100/100/86/86% of patients at month 12. The inactive disease was registrated at 54% (6/11) patients in 6 months, inactive disease and remission was registrated at 86% (6/7) patients in 12 months, at 100% (5/5) patients in 24 months. Nobody had flare of systemic manifestations. The number of AE decreased from 4, 6 to 2, 6 per 100 patients year (p, 0.05) versus rituximab or tocilizumab treatment and antiTNF therapy. Conclusions: AntiTNF therapy may be perspective in patients with sJIA with remission of systemic features and active arthritis. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.1934